1978
DOI: 10.1111/j.1365-2672.1978.tb04222.x
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Inhibitors Formed During the Adventitious Growth of Micro‐organisms in Chicken Liver and Pig Kidney

Abstract: Inhibitory activity (detected by Bacillus cereus var. mycoides), identical with that encountered in survey samples, was induced in homogenized fresh chicken liver or pig kidney samples by incubating at 30°C. relative potency of each of three active components as detected by t.l.c./bio‐autography of extracts of freeze‐dried material was ascertained. Three strains of Streptococcus faecalis and a Lactobacillus sp. were responsible for production of the inhibitory activity, which was not produced by any of these o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

1980
1980
2011
2011

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 10 publications
0
6
0
1
Order By: Relevance
“…False positive results occurred in response to various microbial processes. Firstly, meat discs applied to test plates could already contain natural inhibitors which were presumably derived from earlier bacterial activity within the original sample (Smither, 1978). In support of this theory it was found that these samples were invariably heavily contaminated with bacteria, and that extracts of freezedried sample material were inhibitory to test bacteria.…”
Section: False Positive Resultsmentioning
confidence: 95%
See 3 more Smart Citations
“…False positive results occurred in response to various microbial processes. Firstly, meat discs applied to test plates could already contain natural inhibitors which were presumably derived from earlier bacterial activity within the original sample (Smither, 1978). In support of this theory it was found that these samples were invariably heavily contaminated with bacteria, and that extracts of freezedried sample material were inhibitory to test bacteria.…”
Section: False Positive Resultsmentioning
confidence: 95%
“…The sensitivity of all test plates was monitored by applying 6 mm diameter filter paper discs impregnated with sodium benzylpenicillin (0-01 i.u./disc), streptomycin (0.5 5g/disc) or sulphadimidine (0 5,ug/disc) (Mast Laboratories, Liverpool) which gave annular zones of inhibition of a specified minimum size, that is > 6-8 mm extending from the discs. Electrophoresis and t.l.c./bio-autography Positive FPT samples from both UK-produced and imported meat were examined further at LGC by high voltage electrophoresis (Smither & Vaughan, 1978) to identify antibiotics, and t.l.c./bio-autography (Smither, 1978) to establish the presence of naturally produced inhibitors. The exudates obtained from thawed tissues as well as extracts from freeze-dried material were used for electrophoresis.…”
Section: Control Antibiotic Discsmentioning
confidence: 99%
See 2 more Smart Citations
“…of bactericidal activity (13). Other inhibitory substances have also been recognised and, in particular, lysozyme and similar substances have been found in pig kidneys (18). Lysozyme is released when tissues are thawed from the deep-frozen state and so this particular inhibitory substance could be avoided if fresh, non-frozen, tissues were used for assay.…”
Section: Streptococci Coliforms Bacteroides Clostridiamentioning
confidence: 99%